A (+)‐Larixol Congener with High Affinity and Subtype Selectivity toward TRPC6. (26th April 2018) - Häfner, Stephanie; Burg, Finn; Kannler, Martina; Urban, Nicole; Mayer, Peter; Dietrich, Alexander; Trauner, Dirk; Broichhagen, Johannes; Schaefer, Michael
Abstract: Natural products have many health benefits, and their application can improve the quality of life. Recently, the diterpene (+)‐larixol and its acetylated congeners demonstrated selective inhibition of the second‐messenger‐gated cation channel transient receptor potential canonical 6 (TRPC6) over its close isoforms TRPC3 and TRPC7. Building on this knowledge, we expanded these findings by chemical diversification of (+)‐larixol mostly at position C6. Implementing high‐throughput Ca 2+ FLIPR screening assays and electrophysiological patch‐clamp recordings, we showcase larixyl N ‐methylcarbamate, termedSH045, as a compound with nanomolar affinity and 13‐fold subtype selectivity over TRPC3 in stably expressing HEK293 cells. Expanding on this finding, TRPC6 inhibition was also observed in rat pulmonary smooth muscle cells. Furthermore, treatment of isolated perfused lung preparations withSH045 led to a decrease in lung ischemia‐reperfusion edema (LIRE), a life‐threatening condition associated with TRPC6 that may occur after organ transplantation. Taken together, and given the inexpensive, straightforward, and scalable preparation ofSH045, we report a TRPC6 blocker that holds promise for the translational treatment of LIRE. Abstract : Channeling specificity : The natural product (+)‐larixol was derivatized to obtainSH045, a potent and selective TRPC6 channel blocker, similar to synthetic benchmark blockers such as SAR7334. We assessed the pharmacological properties ofSH045 by electrophysiology as well as in FLIPR assays with HEK293 cells heterologously expressing TRPC6 and in endogenous pulmonary smooth muscle cells. SH045 was also found to decrease edema in explanted murine lungs.